2016
DOI: 10.1371/journal.pone.0166444
|View full text |Cite|
|
Sign up to set email alerts
|

Community ART Support Groups in Mozambique: The Potential of Patients as Partners in Care

Abstract: BackgroundHigh rates of attrition are stymying Mozambique’s national HIV Program’s efforts to achieve 80% treatment coverage. In response, Mozambique implemented a national pilot of Community Adherence and Support Groups (CASG). CASG is a model in which antiretroviral therapy (ART) patients form groups of up to six patients. On a rotating basis one CASG group member collects ART medications at the health facility for all group members, and distributes those medications to the other members in the community. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
50
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 15 publications
7
50
0
1
Order By: Relevance
“…Overall, LTFU in this cohort was high (20.9%), similar to that reported for other clinics in the sub‐district during the same period . In line with some previous publications . LTFU was much lower among clients referred to adherence clubs, when compared to those who stayed in clinic care.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Overall, LTFU in this cohort was high (20.9%), similar to that reported for other clinics in the sub‐district during the same period . In line with some previous publications . LTFU was much lower among clients referred to adherence clubs, when compared to those who stayed in clinic care.…”
Section: Discussionsupporting
confidence: 91%
“…A large study conducted in the Cape Metropole, South Africa, included 3216 clients and showed overall retention in ART care of 95% and 89% at 12 and 24 months respectively, after adherence club referral [10]. Another study from Khayelitsha, Cape Town, showed higher rates of ART client retention over 18 months of follow-up among 502 clients attending adherence clubs compared with 2327 clients not attending clubs (97% vs. 85%) [11][12][13]. In contrast, a recent pragmatic trial conducted in Johannesburg, showed higher LTFU among ART clients in community-based adherence clubs compared with clinic-based adherence clubs.…”
Section: Introductionmentioning
confidence: 99%
“…Second, 50% of CAG members who returned to clinical care did so because of personal reasons or because the group dissolved due to conflicts within the group members. Similar challenges were reported from another setting in Mozambique where eligibility criteria were not always respected [7,10] and in Malawi where some CAGs collapsed due to tensions and interpersonal conflicts within the groups [4]. Reportedly there was need of active involvement of health workers to manage CAGs.…”
Section: Discussionmentioning
confidence: 66%
“…Implementation of patient-centred ART care has been reported from several settings in sub-Saharan Africa [6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Community ART Groups (CAGs) have been piloted in Malawi, Lesotho and Mozambique as a way to reduce patient time and costs spent travelling and queuing for ART refills [7,10,11,18]. In Mozambique the CAG model retained 97.7% and 91.8% of patients at 12, and 48 months [12].…”
Section: Introductionmentioning
confidence: 99%
“…Grimsrud and colleagues recently published two analyses of community-based adherence clubs in South Africa and showed their positive effects on both decentralization and retention in care (measured as loss to follow-up, which they defined as “having no visit in the first 12 weeks of 2014”); of 2133 patients with HIV who participated in community-based adherence clubs, only 6 % of participants were lost to follow-up after a period of 12 months [24, 25]. Similarly, a matched retrospective cohort study in 10 provinces of Mozambique demonstrated lower lost-to-follow-up rates among patients in Community Adherence and Support Groups than among those in individual care (11 versus 26 %) and lower overall attrition (12 versus 28 %), but similar mortality (1 % in both cohorts) [26]. Other studies have shown similar improvement in retention associated with community-based support but without clear mortality benefit [27, 28].…”
Section: Principles Of Community-based Therapymentioning
confidence: 99%